2014
DOI: 10.1007/s11999-013-3374-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Trapeziometacarpal Joint Arthritis: A Historical Perspective

Abstract: Background The trapeziometacarpal (TMC) joint's unique anatomy and biomechanics render it susceptible to degeneration. For 60 years, treatment of the painful joint has been surgical when nonoperative modalities have failed. Dozens of different operations have been proposed, including total or subtotal resection of the trapezium or resection and implant arthroplasty. Proponents initially report high levels of patient satisfaction, but longer-term reports sometimes fail to support initial good results. To date, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…One can argue that, as long as this is achieved, further surgical interventions may be considered superfluous until proven otherwise by properly designed randomized trials. 50 We believe that simple trapeziectomy with HDA is as effective as more complicated procedures. 21 Although it seems unsettling to remove the trapezium and not fill the void, the body has remarkable capacities of self-healing.…”
Section: Trapeziectomymentioning
confidence: 90%
“…One can argue that, as long as this is achieved, further surgical interventions may be considered superfluous until proven otherwise by properly designed randomized trials. 50 We believe that simple trapeziectomy with HDA is as effective as more complicated procedures. 21 Although it seems unsettling to remove the trapezium and not fill the void, the body has remarkable capacities of self-healing.…”
Section: Trapeziectomymentioning
confidence: 90%
“…More recently, with the advancement of small joint implant material technology, several pyrocarbon implant models have been introduced. 10 Woodward et al . describe the practical and theoretical benefits and drawbacks of pyrocarbon implants compared to traditional trapeziectomy, including improved range of motion, decreased postoperative pain and stiffness, and earlier recovery of strength, as well as an increased risk of subluxation of the implant.…”
Section: Pyrocarbon Arthroplastymentioning
confidence: 99%
“… 9 However, there is no current consensus that implant arthroplasty provides superior pain reduction or improved function compared to simple resection arthroplasty. 10 …”
Section: Introduction: Surgical Treatment Options For Trapeziometacarmentioning
confidence: 99%
“…found that the 60-yearold procedure of simple trapezial resection remains the most common surgical procedure for trapeziometacarpal (TMC) joint arthritis, while newer soft tissue and prosthetic arthroplasty methods have not shown any conclusive superiority in terms of pain reduction or increased function. 2 This is in sharp contrast with surgical treatments for other arthritic joints, which have largely evolved from resection arthroplasty to implant arthroplasty. 2 …”
Section: Introductionmentioning
confidence: 99%